Coumarin hybrids: dual-target candidates for future antimicrobial and antitubercular therapies - Bavishi, Abhay; Vala, Hardev; Thakrar, Shailesh; Swami, Sagar; Sarkar, Dhiman; Shukla, Rushit; Kamdar, Jignesh; Shah, Anamik (Future Medicinal Chemistry, 2025)
Aims: This study aimed to synthesize, characterize, and evaluate the antimicrobial and antitubercular activities of two novel series of coumarin-based derivatives (Series 5 and Series 9), focusing on their structure-activity relationship (SAR) and molecular docking interactions with key bacterial enzymes. Materials & methods: Series 5 (5a-5j) and Series 9 (9a-9t) compounds were synthesized and characterized using spectroscopic techniques. Their antimicrobial and antitubercular activities were evaluated against Mycobacterium tuberculosis, Staphylococcus aureus, Bacillus subtilis, and E. coli. IC50 values were determined, and molecular docking studies were conducted to assess binding interactions with M. tuberculosis enoyl-ACP reductase (InhA) and E. coli DNA gyrase B. Results: Series 5 compounds exhibited moderate activity, with 5f, 5 g, 5i, and 5j showing notable inhibition. Series 9 derivatives displayed superior dual-target inhibition, with 9t, 9c, 9a, 9b, and 9p achieving >90% inhibition against S. aureus and B. subtilis. The lowest IC50 against M. tuberculosis was observed for 9c (1.50 mu g/mL), followed by 9a (2.84 mu g/mL) and 9b (2.73 mu g/mL). Molecular docking confirmed strong binding interactions, correlating with observed biological activities. Conclusions: Series 9 compounds, particularly 9t, 9c, and 9a, demonstrate high potential as dual-target antimicrobial drug candidates. Further optimization may enhance their therapeutic efficacy. [GRAPHICS]
Keywords: Antimicrobial activity; antitubercular agents; Coumarin derivatives; Molecular docking studies; structure-activity relationship (SAR); thiophene-based compounds

Regio selective synthesis of pyrazole derivatives of 5-chloro-2-methoxy phenyl hydrazide and their biological evaluation - Bavishi, Abhay; Vala, Hardev; Swami, Sagar; Thakrar, Shailesh; Shah, Anamik; Sarkar, Dhiman (Journal of Heterocyclic Chemistry, 2025)
Present study involves synthesis of derivatives of (5-chloro-2-methoxyphenyl) (5-alkyl-3-(substituted) (phenyl/alkyl)-1H-pyrazol-1-yl) methanones. Structural elucidation of the synthesized compounds was depicted by the data of 1H and 13C NMR, IR, and Mass spectral analysis. The newly synthesized compounds 1a-1d and 2a-2i were screened in vitro against Mycobacterium tuberculosis H37Ra using an established XRMA protocol. Among the screened compounds, 2d, 2f, and 2h showed good percent inhibition against the active stage of M. tuberculosis H37Ra 80.77, 55.70, and 79.54, respectively, at 30 mu g/mL of inhibitor concentration. Further in secondary screening, compound 2d exhibited significant antitubercular activity on the active stage of M. tuberculosis H37Ra with IC50 of 0.208 mu g/mL. The synthesized compounds were also screened for antibacterial activity and found no significant activity against Gram-positive Bacteria Bacillus subtitles and Staphylococcus aureus and Gram negative bacteria Pseudomonas aeruginosa and Escherichia coli at 30 mu g/mL, which confirms the specificity of inhibitory activity against M. tuberculosis and more selectively against the active stage. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.
Keywords: 5-chloro-2-methoxy phenyl hydrazide; antibacterial activity; Antitubercular activity; Biological evaluation; H37Ra; hydrazide; Pyrazole

Synthesis, biological screening, and molecular docking of hybrid pyrazole scaffolds for antitubercular and antimicrobial activity - Bavishi, Abhay; Vala, Hardev; Radadiya, Ashish; Swami, Sagar; Thakrar, Shailesh; Sarkar, Dhiman; Shah, Anamik (ChemistrySelect, 2025)
This study reports the synthesis, characterization, and docking analysis of 21 novel compounds, including asymmetric dihydropyridines (4a-4o) and chalcones (6a-6f), derived from coupling 1,3-(substituted)-diphenyl-1H-pyrazole-4-carbaldehyde with active methylene compounds and 3-acetyl-4-hydroxycoumarin, respectively. Structural confirmation was achieved through 1H and 13C NMR, IR, and mass spectrometry. Biological screening against mycobacterium tuberculosis H37Ra identified compounds 4b, 4d, 4f, 4g , 4i, 4k, 6e, and 6f as significant antitubercular agents. Antibacterial evaluation at 30 mu g/mL showed selective inhibition of gram-positive bacteria, with compound 6e active against Staphylococcus aureus and Bacillus subtilis, and 6f showing activity specifically against S. aureus. Docking studies indicated effective InhA binding (Delta G = -3.52 to -7.27 kcal/mol) and inhibition constants ranging from 2640 to 4.71 mu M. Key binding interactions with residues TYR156 and ILE192 were observed, enhancing affinity, particularly for compound 6e. The SAR analysis emphasized the enhanced antitubercular potency of 2-chloroacetyl and 2,4-dichlorobenzoyl substitutions in the dihydropyridine series, while in the chalcone series, specific substitutions, such as the 3-nitro substitution in 6e, enhance antitubercular and antimicrobial potency due to stronger hydrogen bonding and increased polar surface area, while the 4-fluoro substitution in 6f confers selective activity against S. aureus.
Keywords: 1; 4-dihydropyridine; 4-hydroxy coumarin; Biological activity; In silco studies; Pyrazole